Multiphoton spatial frequency modulated imaging - Wernsing, Keith, author; Bartels, Randy, advisor; Squier, Jeff, committee member; Wilson, Jesse, committee member; Borch, Thomas, committee member (Colorado State University. Libraries, 2023)
Far-field optical microscopy has seen significant development in the last 20 years in its ability to resolve specimen information beyond the diffraction limit. However, nearly all of these super-resolution techniques are predicated on the use of fluorescence as the contrast mechanism in the sample. While the variety of fluorophores available for labeling a sample are a widely-utilized tool, in many instances non-fluorescent contrast mechanisms also provide valuable information. Multiphoton microscopy is one route to probing non-fluorescent contrast mechanisms. It has the benefit of sampling multiple contrast mechanisms at once, including second- and third-harmonic generation and Raman vibrational characteristics, as well as autofluorescence and labeled fluorescence. However, development of super-resolving techniques for coherent scattering processes like harmonic generation or coherent Raman excitation has lagged behind that of incoherent scattering processes like fluorescence. In this work I present the first technique to simultaneously enhance resolution in both real-state (e.g., fluorescence) and virtual-state (e.g. harmonic generation) molecular excitation mechanisms, known as multiphoton spatial-frequency modulated imaging (MP-SPIFI). Standard SPIFI works by projecting spatial cosine patterns onto the sample and gathering object spatial frequency information. Multiphoton SPIFI generates harmonics of these cosine patterns and therein gathers information beyond the frequency passband of the microscope. We demonstrate our initial results with two-photon fluorescence and SHG. An extensive model is built describing the super-resolved image formation process. We then present a method for extending the native, 1D resolution enhancement into two dimensions for an isotropic enhancement. Finally, we present development of two femtosecond, amplified pulsed laser sources tailored to boost SNR in multiphoton processes, through parabolic pulse amplification, and chirped pulse fiber broadening, in order to deliver the high average power & high peak power required by MP-SPIFI for driving nonlinear processes across a line-focus geometry.
Keywords: microscopy; nonlinear; super-resolution; multiphoton; microscope; SPIFI